How the Predict-Observe-Explain (POE) learning strategy remediates students' misconception on Temperature and Heat materials?. (February 2019) - Latifah, S; Irwandani, I; Saregar, A; Diani, R; Fiani, O; Widayanti, W; Deta, U A
Abstract: The purpose of this research is to know how the Predict-Observe-Explain (POE) learning strategy is able to remediate misconception experienced by students. This research was onset by the existence of educators who are not quite precise in choosing learning strategies in accordance with the characteristics of the material, thus resulting in high misconception among students. The research method used was Quasi-Experimental with Non-equivalent Control Group Design. The population of this research was the students of the eleventh grade with 30 students as the sample of the research obtained by using purposive sampling technique. The sample class was given treatment through POE learning strategy. The instrument of data collection used was tested (pretest and post-test). The results showed that POE learning strategy was able to improve students' misconceptions seen from the reduction on the percentage of misconception in problem 2, number 4, and question number 19. It can be concluded that POE learning strategy is effective to remediate the eleventh-grade students' misconception of temperature and heat materials.